Programming languages 16th Brazilian Symposium, SBLP 2012, Natal, Brazil, September 23-28, 2012. Proceedings - Barbosa, Luis Soares; Carvalho Junior, Francisco Heron (Lecture Notes in Computer Science, 2012)
This book constitutes the proceedings of the 16th Brazililan Symposium on Programming Languages, SBLP 2012, held in Natal, Brazil, in September 2012. The 10 full and 2 short papers were carefully reviewed and selected from 27 submissions. The papers cover various aspects of programming languages and software engineering.